An investigation into the use of role- play for enhancing second year non- English major students’ speaking performance at Hanoi University of Business and Technology = Nghiên cứu về việc sử dụng đóng vai tình huống để nâng cao khả năng nói tiếng Anh của - Mai, Thị Lụa Oanh, 1987- (University of Languages and International Studies, 2017)
M.A. Thesis.English Teaching Methodology -- University of Languages and International Studies. Vietnam National University, Hanoi, 2013